Enterprise strategy concept, measurement, and validation: Integrating stakeholder engagement into the firm's strategic architecture. Issue 4 (August 2016) - Vracheva, Veselina; Judge, William Q.; Madden, Timothy
Abstract: A firm's enterprise strategy is its overarching strategic orientation, addressing questions regarding its general purpose and the specific nature of its relationships with stakeholders along two dimensions: (a) scope, which represents the range of stakeholders the organization attempts to serve, and (b) type, which represents the general motivation behind stakeholder initiatives. The corporate social responsibility literature has played an important role in bringing a concern with stakeholder issues; however, this literature does not provide a systematic means of integrating these concerns into the firm's strategic architecture. Enterprise strategy offers a unifying construct, grounded in strategic considerations of both the social and economic demands placed on an organization. However, despite its conceptual importance to strategy and social issues, this construct is empirically underdeveloped. This study develops a reliable and valid measure of the enterprise strategy construct to advance the field's understanding of this increasingly important stream of research. Based on computer-aided text analyses of company letters to stakeholders, we systematically identify terminology that reflects the scope and type of a firm's espoused enterprise strategy. Overall, these data support four fundamental orientations of enterprise strategy: (1) narrow defensive, (2) narrow offensive, (3) broad defensive, and (4) broad offensive.